Analisis Kebutuhan Pengembangan Bahan Ajar Menulis Teks Deskripsi Di Sekolah Dasar - sriyulianingsih; Fahrurrozzi; Nidya Chandra Muji Utami (Jurnal Elementaria Edukasia, 2023)
This study aims to analyze the need for teaching materials that are practical and interesting according to the character of fourth grade elementary school students so that they can increase students' optimism in writing. This study uses descriptive qualitative assessment. This technique is used to observe the need to increase the material for writing descriptive texts in elementary schools. This study is for observation and to form patterns of material in order to facilitate learning to write descriptive texts in elementary schools. The data for this study were obtained through questions and answers to class IV teachers as well as distributing questionnaires to all students at SDN Rawasari 05 Pagi. Through the acquisition of questions and answers, the class teacher at SDN Rawasari 05 Pagi showed the need for companion material for theme 3. So according to the needs analysis questionnaire that was carried out, it was shown that 78% of students needed companion material for the theme book. Through the acquisition of questionnaires and questions and answers, this gives the fact that it is necessary to increase the material for theme 3 thematic books which are dominated by technology in order to support the learning stages which have implications for logic and increase the skills of students. The reviewer hopes that the existence of this needs analysis can help students be able to help deal with conflicts in learning to write descriptive texts and this study is a form of educational participation in elementary schools.